The usual suspects [videorecording (DVD)] - Singer, Bryan. 1965-; Baldwin, Stephen, 1966-; Byrne, Gabriel, 1950-; Palminteri, Chazz; Pollak, Kevin, 1958-; Postlethwaite, Pete; Spacey, Kevin (MGM Home Entertainment, 2002)
Police investigating an exploded boat on a San Pedro pier discover 27 bodies and $91 million worth of drug money. The only survivors are a severely burned Hungarian terrorist and Roger Kint, a crippled con-man. Reluctantly, Kint is pressured into explaining what happened on the boat. His story begins six weeks earlier with five criminals being dragged in by New York police desperate for suspects in a truck highjacking, and ends with the possible identification of a criminal mastermind.